Analysis of Service Quality on Public Satisfaction in Police Record Certificate (SKCK) Services at the West Tarakan Police Office - Samara, Yesika; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the quality of service that is closely related to public satisfication in the process of making a Police Clearance Certificate (SKCK) at the West Tarakan Sectoral Police. The main objective of this research is to determine the extent of service quality at the West Tarakan Sectoral Police based on community satisfication in the process of making a Police Clearance Certificate (SKCK). The method used in this research is a descriptive qualitative method. Researcher are more focused on public services that are observed in depth in accordance with community satisfication which is used as the main measure in this study. Data collection is carried out in the form of interviews and observation of people who apply for the making of Police Clearance Certificate (SKCK) at the West Tarakan Sectoral Police. From this research, the results showed that the community gave a good response to the service of making a Police Clearance Certificate (SKCK) at the West Tarakan Sectoral Police. The services provided are not only limited to making, but also include providing information and education for people who have a lack of understanding about the Police Clearance Certificate (SKCK. A high level of community satisfication has contributed to improving the quality of service of making a Police Clearance Certificate (SKCK) at the West Tarakan Sectoral Police. The renponsiveness of the West Tarakan Sectoral Police creates a positive reputation and the good image for the police institution and builds trust among the community.